# (8x^4+5x^3-5)-(5x^2-6x+4)=

## Simple and best practice solution for (8x^4+5x^3-5)-(5x^2-6x+4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for (8x^4+5x^3-5)-(5x^2-6x+4)= equation:

Simplifying
(8x4 + 5x3 + -5) + -1(5x2 + -6x + 4) = 0

Reorder the terms:
(-5 + 5x3 + 8x4) + -1(5x2 + -6x + 4) = 0

Remove parenthesis around (-5 + 5x3 + 8x4)
-5 + 5x3 + 8x4 + -1(5x2 + -6x + 4) = 0

Reorder the terms:
-5 + 5x3 + 8x4 + -1(4 + -6x + 5x2) = 0
-5 + 5x3 + 8x4 + (4 * -1 + -6x * -1 + 5x2 * -1) = 0
-5 + 5x3 + 8x4 + (-4 + 6x + -5x2) = 0

Reorder the terms:
-5 + -4 + 6x + -5x2 + 5x3 + 8x4 = 0

Combine like terms: -5 + -4 = -9
-9 + 6x + -5x2 + 5x3 + 8x4 = 0

Solving
-9 + 6x + -5x2 + 5x3 + 8x4 = 0

Solving for variable 'x'.

The solution to this equation could not be determined.`